2019
DOI: 10.1121/1.5099164
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond sensitivity to envelope interaural time differences in rats

Abstract: Currently, there is controversy around whether rats can use interaural time differences (ITDs) to localize sound. Here, naturalistic pulse train stimuli were used to evaluate the rat's sensitivity to onset and ongoing ITDs using a two-alternative forced choice sound lateralization task. Pulse rates between 50 Hz and 4.8 kHz with rectangular or Hanning windows were delivered with ITDs between ±175 μs over a near-field acoustic setup. Similar to other mammals, rats performed with 75% accuracy at ∼50 μs ITD, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 24 publications
7
45
0
Order By: Relevance
“…This study is the first demonstration that, at least in rats, severely degraded auditory experience in early development does not inevitably lead to impaired binaural time processing in adulthood. In fact, the ITD thresholds of our NDCI-B rats (≈ 50 µs) were as good as the ITD thresholds of NH-B rats Li et al (2019), and many times better than those typically reported for early deaf human CI patients with thresholds often too large to measure (Litovsky et al 2010;Gordon et al 2014;Ehlers et al 2017). The good performance exhibited by our NDCI-B animals raises the important question of whether early deaf human CI patients might perhaps also be able to achieve near normal ITD sensitivity if supplied with optimal bilateral CI stimulation capable of delivering adequate ITDs from the first electric stimulation even in the absence of hearing experience during a period what has been thought to be critical for the development of ITD sensitivity.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…This study is the first demonstration that, at least in rats, severely degraded auditory experience in early development does not inevitably lead to impaired binaural time processing in adulthood. In fact, the ITD thresholds of our NDCI-B rats (≈ 50 µs) were as good as the ITD thresholds of NH-B rats Li et al (2019), and many times better than those typically reported for early deaf human CI patients with thresholds often too large to measure (Litovsky et al 2010;Gordon et al 2014;Ehlers et al 2017). The good performance exhibited by our NDCI-B animals raises the important question of whether early deaf human CI patients might perhaps also be able to achieve near normal ITD sensitivity if supplied with optimal bilateral CI stimulation capable of delivering adequate ITDs from the first electric stimulation even in the absence of hearing experience during a period what has been thought to be critical for the development of ITD sensitivity.…”
Section: Discussionsupporting
confidence: 57%
“…High frequency "envelope" ITD sensitivity is also bound to be of great importance in prosthetic hearing given that CIs rarely reach the apex of the cochlea. In Li et al (2019) we recently demonstrate that NH rats can use ITD cues for 2AFC sound lateralization tasks and thus conclude that, at least to broadband clicks, rats show ITD sensitivity. Here, we focused on broad-band acoustic or electrical pulse stimuli which provide plenty of "onset" and "envelope"…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Advances in neural implant and electrical stimulation technologies, such as cochlear implants (CIs) and vagal nerve stimulators, increasingly rely on concurrent neural stimulation and recordings to either assess functional transformations between connected brain regions ( Lim and Anderson, 2007 ; Kral et al, 2009 ; Atencio et al, 2014 ; Hancock et al, 2017 ; Vollmer, 2018 ; Li et al, 2019 ) or to optimize electrical stimulation via closed-loop feedback control ( Wilson et al, 1991 ; Schachter and Saper, 1998 ; Dhillon and Horch, 2005 ; Lebedev and Nicolelis, 2006 ; O’Doherty et al, 2011 ; Mc Laughlin et al, 2012 ; Hartmann et al, 2014 ). In such applications, capacitive and inductive coupling between the stimulating and recording electrodes leads to stimulus-evoked artifacts in the extracellular recordings that are often several orders of magnitude larger (i.e., milli-volts) than the extracellular neural signals (typically micro-volts).…”
Section: Introductionmentioning
confidence: 99%